Assessing The Impact of Financial Service Digitalization on SME Businesses In Lagos, Nigeria - Olatunji, Fadeyi; Sajuyigbe, Ademola Samuel; Tella, Rahman Adeniran; Oke, Oluwakayode David; Babalola, Olusola Adebola; Adebayo , Wahab (Program MM Universitas Surabaya, 2025)
Purpose: This paper examines the impact of digitalization on SMEs in Lagos Nigeria, especially in digital financial services. Method: The respondents for this study were 150 owners /managers of SMEs in Lagos, Nigeria and data were analyzed descriptively and inferentially using the chi-square test. The research adopts a quantitative research strategy to analyze the difference between SME performance before and after adopting the technology, analyze the degree of technology adoption by the SMEs, and Quantitative evaluation of the advantages of digital financial services. Result: The study found that digitalization has improved SME operations, enhancing efficiency, competitiveness, and access to financial services. However, challenges like internet connectivity and security issues remain unaddressed, necessitating targeted interventions and support strategies. To maximize digitalization's benefits, the study recommends government-led awareness campaigns to highlight the advantages of digital financial services for SMEs. Additionally, partnerships with telecom firms and government agencies should be established to expand broadband access and improve internet reliability in underserved areas. Finally, training programs for SME owners and staff are essential to ensure effective use of these financial services.